Urban Transformation in Cirebon: Celebrity Endorsement, Global Pop Culture, and Youth Consumption - Farida Nurfalah; M. Nuruzzaman; Rifka Noviani Santika; Mohd Naufal Bin Yunus (Riviera Publishing, 2026)
In the era of global pop culture and digital media proliferation, celebrity endorsement has become a key strategy in marketing communication, particularly for engaging youth consumers who are deeply embedded in fandom communities. This research examines celebrity endorsement as a communication management practice by analyzing how the global K-pop group Blackpink functions as a brand ambassador for Oreo among teenage consumers in Cirebon City, Indonesia. Employing a qualitative case study design, the research draws on semi-structured interviews, non-participant observation, and documentation of Instagram-based promotional materials. The findings demonstrate that Blackpink performs three interrelated communicative roles: visual testimonial provision, endorsement and symbolic reinforcement, and narrative centrality within brand communication. Rather than relying on informational persuasion, Oreo strategically manages meaning through visual symbolism, fandom-oriented engagement, and platform-specific narratives that enable teenagers to co-create brand meaning. Conceptually, the study advances communication management scholarship by positioning celebrity endorsement as a process of meaning management, stakeholder engagement, and strategic narrative construction, particularly within secondary urban contexts shaped by global media flows.